2022
DOI: 10.1002/jor.25431
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous injection of adipose‐derived mesenchymal stromal cells benefits gait and inflammation in a spontaneous osteoarthritis model

Abstract: Osteoarthritis (OA) is a leading cause of morbidity among aging populations, yet symptom and/or disease-modification remains elusive. Adipose-derived mesenchymal stromal cells (adMSCs) have demonstrated immunomodulatory and anti-inflammatory properties that may alleviate clinical signs and interrupt disease onset and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Mobility assessments via treadmill-gait and voluntary weight-bearing systems were utilized to identify potential alterations in gait parameters given the unilateral removal of the IFP/SC. The changes in gait over time for stride length, stance, and propel were an expected function of growth between 3 and 7 months of age [47][48][49]. In spite of our documented decrease in structural OA, removal of the IFP/SC compared to the limb with the native IFP/SC did not result in any changes in midline distance, stride length, swing, stance, brake, or propel time.…”
Section: Treadmill-based Gait Analysesmentioning
confidence: 58%
“…Mobility assessments via treadmill-gait and voluntary weight-bearing systems were utilized to identify potential alterations in gait parameters given the unilateral removal of the IFP/SC. The changes in gait over time for stride length, stance, and propel were an expected function of growth between 3 and 7 months of age [47][48][49]. In spite of our documented decrease in structural OA, removal of the IFP/SC compared to the limb with the native IFP/SC did not result in any changes in midline distance, stride length, swing, stance, brake, or propel time.…”
Section: Treadmill-based Gait Analysesmentioning
confidence: 58%
“…Additionally, a recent short-term study of MSCs-IVt period injections (4 weeks) did not show changes in AC. However, gait performance improved, potentially due to a systemic immunomodulatory effect, as indicated by the suppression of serum inflammatory markers (MCP-1, TNF, and PG(E) 2 ), according to the authors [18]. Collectively, these findings suggest that due to the transient nature of MSCs' effects, therapies aiming to improve AC health in OA may be more effective with long-term protocols and periodic injections, regardless of transplant route.…”
Section: Discussionmentioning
confidence: 81%
“…Studies reporting positive effects of MSCs-IAt treatment on AC typically rely on inflammatory-driven OA animal models induced by joint enzymatic injections, severe joint destabilization surgery, or MSC transplantation during the initial inflammatory response caused by the model induction [5]. However, fewer studies have explored MSCs-IVt for OA treatment [12][13][14][15][16][17][18], and the ones reporting beneficial effects on AC have also used similar approaches as MSCs-IAt studies [13,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As expected given our study in a male cohort of guinea pigs ( 21 ), treadmill and weight bearing analyses demonstrated no unilateral differences between hindlimbs in female animals. The longitudinal differences across time that were seen in gait and voluntary weight-bearing movement for both sexes were anticipated due to long-bone growth during 3 to 7 months of age ( 21 , 22 , 43 , 45 ).…”
Section: Discussionmentioning
confidence: 99%